2008
DOI: 10.1007/s00381-008-0678-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar pilocytic astrocytoma presenting with intratumor bleeding, subarachnoid hemorrhage, and subdural hematoma

Abstract: The authors' case is the first report with a presentation including ITB, SAH, and SDH. The presumed mechanism of the SAH and SDH was leaking of the ITB into subarachnoid and subdural spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…A particular clinicopathological presentation of PAs might be associated with fatal haemorrhages, which are most often subarachnoid (SAH) [34,46,54,61,64]. Such tumour manifestation is less commonly observed in PMA [35,89].…”
Section: Prognosismentioning
confidence: 99%
“…A particular clinicopathological presentation of PAs might be associated with fatal haemorrhages, which are most often subarachnoid (SAH) [34,46,54,61,64]. Such tumour manifestation is less commonly observed in PMA [35,89].…”
Section: Prognosismentioning
confidence: 99%
“…Once considered an infrequent occurrence, 8,21,23 spontaneous hemorrhage in PAs has become more recognized 1,9,11,12,15,19,24 and can present as an acute neurosurgical emergency. In a retrospective review of 138 cases of PAs, White et al 24 reported that 8% of their patients had a concurrent hemorrhage at presentation as assessed by CT and MRI and confirmed by pathological examination of the resected tumor.…”
Section: Discussionmentioning
confidence: 99%
“…described a case of a hemorrhagic cerebellar pilocytic astrocytoma in a 15-month-old boy [6]. Lyons reported on a case of a spontaneous intracerebral hemorrhage in association with a pilocytic astrocytoma in a 75-year-old man [8].…”
Section: Discussionmentioning
confidence: 99%
“…We aim to present the case of an adult harboring a posterior fossa pilocytic astrocytoma presenting in an acute fashion with a rapidly deteriorating neurological exam after spontaneous intratumoral hemorrhage. Cases of hemorrhagic presentation of these tumors have been reported in the literature [1][2][3][4][5][6][7][8][9][10][11], although they are quite rare. The vast majority of pilocytic astrocytomas are not associated with hemorrhage, leading one to infer that a small sub-population of these tumors may have inherent features making them more susceptible to hemorrhagic complications.…”
Section: Introductionmentioning
confidence: 99%